Investigation of a 3D-Magnetic Flux PMSM With High Torque Density for Electric Vehicles - Chen, Hao; Demerdash, Nabeel A. O.; EL-Refaie, Ayman M.; Guo, Youguang; Hua, Wei; Lee, Christopher H. T. (IEEE transactions on energy conversion, 2022)
This paper presentsan investigation of a 3D-magnetic flux permanent magnet synchronous motor (3D-MF PMSM) used for electric vehicle applications. The investigated 3D-MF PMSM consists of an integrated radial-flux and axial-flux structure. It has two radial-flux air-gaps and two axial-flux air-gaps, as well as a toroidal winding wound stator. The integrated structure helps to concentrate all the flux within the motor to maximize torque production. Moreover, there are no end-windings in this motor and all the stator windings effectively are used in torque production. A comprehensive performance evaluation, in terms of the back-electromotive force, average output torque, cogging torque, torque ripple, flux-weakening capability, etc., of the investigated 3D-MF PMSM is conducted. An interior PMSM is purposely included as a benchmark for comparison. The results show that compared to the benchmark interior PMSM, the original 3D-MF PMSM exhibits significantly improved torque density, higher power factor, and higher efficiency, but suffers from serious cogging torque and torque ripple. Accordingly, a skewed arrangement is introduced to the 3D-MF PMSM. As a result, the cogging torque and torque ripple are significantly reduced.